Pengembangan Media Lupas (Ludo IPAS) di Kelas IV SD Negeri 28 Pontianak Selatan - Novada, Cristine; Kartono, Kartono; Salimi, Asmayani (FONDATIA, 2023)
This study aims to develop and produce valid, practical and effective Lupas (Ludo IPAS) learning media by using the type of research and development (Research and Development), using mixed methods (mix methods) and the ADDIE model, namely analysis, design, development, implementation, and evaluation. Implementation was carried out at SDN 28 South Pontianak on Class IV students as many as 27 respondents. The results of the research are in the form of Lupas (Ludo IPAS) media product development in learning "How to Get All Our Needs". The acquisition of material validity results of 86% is categorized as "very valid" and the acquisition of media validity of 91% is categorized as "very valid". The acquisition of the level of practicality by students of 82% is categorized as "very practical" and by teachers of 86% is categorized as "very practical". While the acquisition of effectiveness of 85% is categorized as "Effective". Based on the overall acquisition, it can be seen that the Lupas (Ludo IPAS) media is valid, practical and effective for use in learning activities on the material "How to Get All Our Needs" in grade IV elementary school.